Clinical study of babies born through meconium stained amniotic fluid - Y. M., Shilpasri; B., Madhurya (International Journal of Contemporary Pediatrics, 2019)
Background: Meconium stained amniotic fluid has been considered a sign of fetal distress and associated with poor fetal outcome, but others considered meconium passage by fetus is physiological phenomena and produce environmental hazards to fetus before birth. Such magnitude of different opinion was the object behind taking up of this study and aim was to find out incidence and effect of meconium in terms of morbidity and mortality. Methods: Two hundred babies born with meconium stained amniotic fluid considering the inclusion and exclusion criteria from December 2012 to June 2013 in the Department of Paediatrics, Cheluvamba hospital attached to Mysore Medical College and Research Institute, Mysore. Fetal monitoring, mode of delivery, Apgar score, birth weight, resuscitation of baby are noted. All babies followed-up up to 1st week of neonatal life. Results: In present study 200 babies born through meconium stained amniotic fluid was randomly selected-thin 37% and thick 63%. Major complications like birth asphyxia, meconium aspiration syndrome, early neonatal death seen in 5.5% (11 cases), morbidity in 37%, 12.5% in thin and 24.5% in thick MSAF. Causes of death were meconium aspiration syndrome in 3 cases, sepsis in 1 case, pneumonia in 1 case and birth asphyxia in 6 cases. Conclusions: Immediate airway management, need for suction and intubation should be guided by state of newborn rather than presence of meconium. Timely diagnosis and management of meconium stained amniotic fluid may improve fetal outcome. From present study authors conclude that MSAF adversely affect fetal outcome mostly by thick meconium.